An Analysis of Aisha's Hadith regarding the Night Prayer of the Prophet. - Nurdin, Abdul Haris; Dr. H. Erwin Hafid, Lc, M.Th.I, M.Ed. (Pascasarjana, Universitas Islam Negeri Alauddin Makassar, 2023)
This study focuses on the Prophet's night prayer, using the tahlili syarah method. It has been discovered that the Prophet's night prayer never exceeded thirteen rak'ahs, which were performed in a specific pattern. He would pray four rak'ahs, followed by another four rak'ahs, and then three rak'ahs of Witr. The Hanafiyyah scholars interpret this hadith textually, believing that the Prophet prayed four rak'ahs with one salutation, followed by four rak'ahs with one salutation, and then three rak'ahs. Other scholars interpret the Hadith intertextually, believing that the Prophet prayed four rak'ahs, then another four rak'ahs, with a salutation at every two rak'ahs. It is also important to note that the Hanafiyyah scholars do not consider 'A'ishah's Hadith applicable to the tarawih prayer. This is because the tarawih prayer is performed in the congregation, which should be made lighter. The text of 'Asiyah's hadith indicates that the prayer is long.